Seroprevalence of SARS-CoV-2 Infection in the Colombo Municipality Region, Sri Lanka - Jeewandara, Chandima; Guruge, Dinuka; Abyrathna, Inoka Sepali; Danasekara, Saubhagya; Gunasekera, Banuri; Pushpakumara, Pradeep Darshana; Madhusanka, Deshan; Jayathilaka, Deshni; Ranasinghe, Thushali; Somathilake, Gayasha; Tanussiya, Shyrar; Jayadas, Tibutius Tanesh; et al. (Frontiers in Public Health, 2021)
Background As the Municipality Council area in Colombo (CMC) experienced the highest number of cases until the end of January 2021, in Sri Lanka, we carried out a serosurvey prior to initiation of the vaccination program to understand the extent of the SARS-CoV-2 outbreak. Methods SARS-CoV-2 seropositivity was determined in 2547 individuals between the ages of 10 to 86 years, by the Wantai total antibody ELISA. We also compared seroprevalence using the haemagglutination test (HAT) to evaluate its usefulness in carrying out serosurveys. Results The overall seropositivity rate was 24.46%, while seropositivity by HAT was 18.90%. Although The SARS-CoV-2 infection detection rates by PCR were highest in the population between the ages of 20 to 60 years of age, there was no statistically significant difference in the seropositivity rates in different age groups. For instance, although the seropositivity rate was highest in the 10 to 20 age group (34.03%), the PCR positivity rate was 9.80%. Differences in the PCR positivity rates and seropositivity rates were also seen in 60 to 70-year-olds (8.90% vs 30.4%) and in individuals >70 years (4.10% vs 1.20%). The seropositivity rate of the females was 29.70% (290/976), which was significantly higher (p<0.002) than in males 21.2% (333/1571). Conclusions A high seroprevalence rate (24.5%) was seen in all age groups in the CMC suggesting that a high level of transmission was seen during this time. The higher PCR positivity rates between the ages of 20-60 is likely to be due to increased testing carried out in the working population. Therefore, the PCR positivity rates, appear to underestimate the true extent of the outbreak and the age groups which were infected.